Impact of patient characteristics on innate immune responses and inflammasome activation in ex vivo human lung tissues infected with influenza A virus - Huang, Chung-Guei; Wu, Yi-Cheng; Hsieh, Ming-Ju; Lin, Ya-Jhu; Hsieh, Tzu-Hsuan; Huang, Po-Wei; Yang, Shu-Li; Tsao, Kuo-Chien; Shih, Shin-Ru; Lee, Li-Ang (Frontiers in Cellular and Infection Microbiology, 2023)
Background Influenza A virus (IAV) infection poses a persistent global health challenge, necessitating a nuanced grasp of host immune responses for optimal interventions. While the interplay between aging, immunosenescence, and IAV is recognized as key in severe lower respiratory tract infections, the role of specific patient attributes in shaping innate immune reactions and inflammasome activity during IAV infection remains under-investigated. In this study, we utilized an ex vivo infection model of human lung tissues with H3N2 IAV to discern relationships among patient demographics, IAV nucleoprotein (NP) expression, toll-like receptor (TLR) profiles, PD-1/PD-L1 markers, and cytokine production. Methods Our cohort consisted of thirty adult patients who underwent video-assisted thoracoscopic surgery during 2018–2019. Post-surgical lung tissues were exposed to H3N2 IAV for ex vivo infections, and the ensuing immune responses were profiled using flow cytometry. Results We observed pronounced IAV activity within lung cells, as indicated by marked NP upregulation in both epithelial cells (P = 0.022) and macrophages (P = 0.003) in the IAV-exposed group relative to controls. Notably, interleukin-2 levels correlated with variations in TLR1 expression on epithelial cells and PD-L1 markers on macrophages. Age emerged as a modulating factor, dampening innate immune reactions, as evidenced by reduced interleukin-2 and interferon-γ concentrations (both adjusted P < 0.05). Intriguingly, a subset of participants with pronounced tumor necrosis factor-alpha post-mock infection (Cluster 1) showed attenuated cytokine responses in contrast to their counterparts in Cluster 2 and Cluster 3 (all adjusted P < 0.05). Individuals in Cluster 2, characterized by a low post-mock infection NP expression in macrophages, exhibited reduced variations in both NP and TLR1–3 expressions on these cells and a decreased variation in interleukin-2 secretion in comparison to their Cluster 3 counterparts, who were identified by their elevated NP macrophage expression (all adjusted P < 0.05). Conclusion Our work elucidates the multifaceted interplay of patient factors, innate immunity, and inflammasome responses in lung tissues subjected to ex vivo H3N2 IAV exposure, reflecting real-world lower respiratory tract infections. While these findings provide a foundation for tailored therapeutic strategies, supplementary studies are requisite for thorough validation and refinement.